Implementasi Manajemen Kurikulum Merdeka Belajar dalam Peningkatan Mutu Pendidikan di SMA Negeri 1 Bandar - Gustinar Napitupulu; Mardin Silalahi; Sariaman Gultom (Departement of Mathematics Education, 2023)
This study aims to determine the planning, implementation, and evaluation of the curriculum. This study used a qualitative research approach with 6 informants consisting of the principal, vice principal for curriculum, and teachers of SMA Negeri 1 Bandar. Data collection techniques through three ways, namely observation, document study, and interviews. The data analysis technique goes through three stages, namely data reduction, data analysis, and drawing conclusions. The results of this study indicate that: (1) Planning for the Free Learning Curriculum in Improving the Quality of Education at SMA Negeri 1 Bandar carried out several plans, namely: a). There is a thorough evaluation of student needs, educational developments, and the demands of the world of work. b). Collaboration between vice principals, teacher teams, and education experts. (2) Implementation of the Free Learning Curriculum in Improving the Quality of Education in SMA Negeri 1 Bandar is carried out by: a). Engage training and support to teachers in designing and implementing innovative and relevant learning. b). Teachers are encouraged to use active, collaborative, and contextual learning methods. (3) Evaluation of the Free Learning Curriculum in Improving the Quality of Education at SMA Negeri 1 Bandar is carried out by: a). Sustainable and holistic, b). Evaluation of curriculum impact, c) Evaluation of Teacher Professional Development, d) Evaluation of innovative learning methods, increasing teacher competence, mastery of material, student involvement in learning and evaluation of the impact of the Merdeka Learning program which has been implemented on an ongoing basis.